Fenomena Seni Pertunjukan Sintren Pesisiran dan Pemberdayaan Masyarakat melalui Pedekatan Antropologis - Kukuh Pamuji (Institut Seni Indonesia Surakarta, 2022)
The phenomenon of coastal sintren performing arts in the border areas of West Java (Cirebon and Indramayu) and Central Java (Brebes, Tegal, Pemalang) which has local genius by carrying out cultural transformations between traditions and mystical traditional arts transforming with modern culture as an effect of urban culture, finally with the transformation of culture will be transformed into urban culture. The problems that exist in the Sintren Pesisitran art community include: (1) the lack of support for the development and preservation of coastal traditional arts, (2) How the art of performing the Coastal Sintren can holistically rediscover the essence of aspects of cultural expression and the development of other creative aspects. This empowerment program is carried out through various mentoring programs including; (1) empowering creative human resources, (2) choreography training, musical instruments, (3) costume assistance for several Sintren Pesisiran communities. The results of community empowerment assistance, including: The performing arts of coastal sintren can be studied holistically, aspects of art as expression, art as pragmatics, anthropological and sociological studies. Pragmatically, this typical coastal art performs practical activities for various aspects of interest. It was then realized by the performing arts community that their creative activities are not just expressions. Social aspects are also interpreted more broadly when we look at the educational aspect, of course with multidimensional and multi-interpreted discourses.